2017
DOI: 10.1021/acs.inorgchem.6b01624
|View full text |Cite
|
Sign up to set email alerts
|

Solution Species and Crystal Structure of Zr(IV) Acetate

Abstract: Complex formation and the coordination of zirconium with acetic acid were investigated with Zr K-edge extended X-ray absorption fine structure spectroscopy (EXAFS) and single-crystal diffraction. Zr K-edge EXAFS spectra show that a stepwise increase of acetic acid in aqueous solution with 0.1 M Zr(IV) leads to a structural rearrangement from initial tetranuclear hydrolysis species [Zr(OH)(OH)] to a hexanuclear acetate species Zr(O)(OH)(CHCOO). The solution species Zr(O)(OH)(CHCOO) was preserved in crystals by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 45 publications
8
100
1
Order By: Relevance
“…Previous research has systematically studied the structure of Zr IV multinuclear species in various solutions from different precursor salts by EXAFS, mass‐spectrometry, and computational studies, which indicated that zirconium shows a strong tendency toward hydrolysis and polymerization. There is a common agreement that the tetramer complex Zr 4 (OH) 8 (H 2 O) 16 , with extraordinary stability, is the dominant hydrolysis species in zirconium aqueous solution, whereas the extended oligomer chain Zr 8 O 28 (NO 3 ) 8 is the dominant species in Zr oxynitrate in methanol or Zr acetate aqueous solution . In the current study, it is clear that neither the tetramer species nor the extended oligomer chains explain the higher peak area of 3.5 Å than 2.2 Å, which shows disagreement with the experimental PDF of the dissolved Zr IV precursor in DMF and HCl solution (Figure S9, S10).…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…Previous research has systematically studied the structure of Zr IV multinuclear species in various solutions from different precursor salts by EXAFS, mass‐spectrometry, and computational studies, which indicated that zirconium shows a strong tendency toward hydrolysis and polymerization. There is a common agreement that the tetramer complex Zr 4 (OH) 8 (H 2 O) 16 , with extraordinary stability, is the dominant hydrolysis species in zirconium aqueous solution, whereas the extended oligomer chain Zr 8 O 28 (NO 3 ) 8 is the dominant species in Zr oxynitrate in methanol or Zr acetate aqueous solution . In the current study, it is clear that neither the tetramer species nor the extended oligomer chains explain the higher peak area of 3.5 Å than 2.2 Å, which shows disagreement with the experimental PDF of the dissolved Zr IV precursor in DMF and HCl solution (Figure S9, S10).…”
Section: Resultscontrasting
confidence: 71%
“…This indicates the predominant presence of UiO‐66 SBU structures in ZrCl 4 precursor solution without addition of organic ligand. This hexanuclear zirconium cluster has previously been observed as the dominant structure in Zr IV aqueous solution, with addition of acetic acid (pH 1.5), by EXAFS . However, the present PDF analysis is the first evidence of this SBU existing at room temperature in the metal source precursor solution usually used for UiO‐66 synthesis.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…The Zr ions are connected by hydroxo-bridges. [29][30][31] The stability of the cyclic tetramer has been also proven by computation. 32 The polymerization reaction of tetramers into edge-sharing chains of tetramers 33 occurs depending on the concentration, the pH, and experimental conditions.…”
Section: Fig 3 Like Inmentioning
confidence: 99%
“…Then, in 1985, a planar pentagonal {Hf 6 } cluster was reported . Although the octahedral hexameric ZrOCs (as well as HfOCs) have been synthesized by non‐aqueous hydrothermal methods for a long time and are common nodes of Zr‐based MOFs, only very recently was an octahedral {Zr 6 } cluster stabilized by glycine ligands isolated from water . Recently, Soderholm et al.…”
Section: Introductionmentioning
confidence: 99%